Novel radiopharmaceuticals: characterization, substitution kinetics and biological evaluation of tricarbonyl complexes of Rhenium(I) - Schutte, Marietjie (University of the Free State, 2011)
Over the past few years, significant interest has been shown in Rhenium and Technetium tricarbonyl complexes of the form fac-[M(L,L’-bid)(CO)3(X)]n (M = Tc(I) and Re(I), (L,L’-bid) = different donor atom bidentate ligands, X = range of monodentate ligands), as potential diagnostic and therapeutic radiopharmaceuticals, respectively. This is mainly due to the discovery of the fac-[M(CO)3(H2O)3]+ synthon with the inert fac- [M(CO)3]+ core and the labile water molecules. These main characteristics make the synthons very attractive for application in nuclear medicine. Overall, the idea of this study was to gain further insight into the chemistry, coordination and kinetic behaviour of complexes containing the fac-[M(CO)3]+ core. From this idea, it was decided to synthesize a few novel ligand systems. This include N-benzylindole- 2,3-dione, N,N’-bis(2-pyridylmethyl)-2-aminoethanol, N,N’-bis(2-pyridylmethyl)-2-aminopropanol, N,N’-bis(2-pyridylmethyl)-2-aminobutanol, N’-(2-(1H-imidazol-4-yl)ethyl)- N3,N3-bis(pyridine-2-ylmethyl)-propane-1,3-diamine, 2-(3-(bis(pyridin-2-yl)methyl)- amino)propylamino)-acetic acid, N-(2-(1H-imidazol-4-yl)ethyl)pyrrolidine-2-carboxamide, N’-(2-(1H-imidazol-4-yl)ethyl)benzohydrazide and N-(pyridin-2-ylmethyl)nicotinamide. Some of these ligands were successfully coordinated to the fac-[Re(CO)3]+ core as well. The ligand systems, as well as these Rhenium(I) compounds, were sent for in vitro testing. The ligand systems synthesized were designed with the idea to be potentially biologically active by itself as well. A range of tricarbonyl complexes, of the form fac-[Re(L,L’-bid)(CO)3X], were synthesized by using a wide variety of bidentate ligands (L,L’-bid), with systematically chosen donor atoms. The bidentate ligands include 2,2’-bipyridine-3,3’-dicarboxylic acid, 2,5-pyridinedicarboxylic acid, 8-hydroxyquinoline, 5-chloro-8-hydroxyquinoline, 5,7-dimethyl-8-hydroxyquinoline, tropolone, isatin, 5-nitroisatin, 5-(trifluoromethoxy)- isatin, benzohydroxamic acid, 3-hydroxyflavone, chrysin and bis(diphenylphosphino)- propylamine, X = variety of monodentate ligands and n = 0, 1. During the study, four 99mTc complexes were successfully synthesized, including fac- [99mTc(2,5-PicoH)(CO)3(H2O)], fac-[99mTc(Trop)(CO)3(H2O)], fac-[99mTc(Cl ox)(CO)3(H2O)] and fac-[99mTc(DMe-ox)(CO)3(H2O)]. We were unable to isolate the 99mTc compounds of five different ligand systems, even though the Rhenium analogues were successfully synthesized. This once again proved the similarities in chemistry of Rhenium and Technetium, but that this cannot always be assumed. The lability and mechanism of substitution of the methanol ligand by simple monodentate nuclephiles were evaluated. The methanol substitution reactions, between fac-[Re(2,5-PicoH)(CO)3(MeOH)], fac-[Re(Isa)(CO)3(MeOH)] and fac- [Re(Trop)(CO)3(MeOH)] and the variety of incoming ligands (bromide ions, iodide ions, pyridine, 4-dimethylaminopyridine, imidazole, thiocyanate ions, thiourea and 1-methyl-2- thiourea), all pointed towards an interchange associative or associative type mechanism, predicted from the negative ΔS‡ values calculated. High pressure studies were performed and from the results, an interchange dissociative type mechanism was assigned, with a definite decrease in the reaction rate with an increase in pressure. These results once again proved the only way to unambiguously determine a reaction mechanism, is by means of the high pressure studies. For the first time ever, the water substitution reaction of a compound of the type fac-[Re(L,L’-bid)(CO)3(H2O)] was performed. The reaction between fac- [Re(Trop)(CO)3(H2O)] and thiocyanate ions were followed. Overall the water substitution reaction has larger k1 and K1 values compared to the corresponding methanol substitution reaction, therefore indicating a faster reaction and a more stable product. These are especially great results for the use in nuclear medicine. From the kinetic studies performed, excellent results were obtained of which one is the definite increase in reaction rate from N,O- to O,O’-donor bidentate ligand compounds. This was expected due to the increase in electron density on the metal centre and therefore the weakening of the Re-MeOH bond. The O,O’-donor bidentate ligands activate the Re(I) metal centre to an even greater extent, as was reported before. The ‘3+1’ concept was proven, from the synthesis of fac-[Re(PMAEth-An)(CO)3][NO3], fac- [Re(PMAProp-His)(CO)3][NO3] and fac-[NEt4]/[Na][Re(NTA-An)(CO)3], by linking a biologically active ligand to the backbone of a tridentate ligand that is coordinated to the fac-[Re(CO)3]+ core. This leaves huge scope for potential radiopharmaceutical agents of this type. Four of the ten crystal structure reports in this study are monodentate substituted complexes, which serves as further confirmation of the kinetic end products.

Die laaste paar jaar het die belangstelling in Renium en Tegnesium trikarboniel komplekse, fac-[M(CO)3]+ (M = Tc(I) en Re(I)), beduidend toegeneem as potensiële diagnostiese en terapeutiese radiofarmaseutiese middels onderskeidelik. Dit is grotendeels agv die ontdekking van die fac-[M(CO)3(H2O)3]+ moïeteit. Verskeie belowende komplekse, wat die trikarboniel moïeteit bevat, is al gesintetiseer en twee van die hoof eienskappe wat die moïeteit so aantreklik maak vir die gebruik in kliniese medisyne, is die inerte fac-[M(CO)3]+ kern en die labiele water molekule. Die algehele motief van die studie was om meer inligting en beter insig ten opsigte van die chemiese, koördinatiewe en kinetiese gedrag van die fac-[M(CO)3]+ tipe komplekse te verkry. Vanaf hierdie uitgangspunt, is daar besluit om `n reeks nuwe vry ligande te sintetiseer, om te gebruik as potensiële biologies-aktiewe verbindings self, en om te koordineer met fac-[Re(CO)3]+ om sodoende `n potensiële aktiewe kompleks te verkry. Die ligande sluit in N-bensielindol-2,3-dioon, N,N’-bis(2-piridielmetiel)-2-aminoetanol, N,N’-bis(2-piridielmetiel)-2-aminopropanol, N,N’-bis(2-piridielmetiel)-2-aminobutanol, N’- (2-(1H-imiedasool-4-iel)etiel)-N3,N3-bis(piridien-2-ielmetiel)-propaan-1,3-diamien, 2-(3- (bis(piridien-2-iel)metiel)amino)propielamino)-asynsuur, N-(2-(1H-imiedasool-4- iel)etiel)pirrolidien-2-karboksamied, N’-(2-(1H-imiedasool-4-iel)etiel)bensohidrasied en N-(pyridin-2-ielmetiel)nikotinamied. Sommige van die ligande is suksesvol gekoördineer met die fac-[Re(CO)3]+ moïeteit en die ligand sisteme sowel as die Rhenium(I) komplekse is gestuur vir in vitro toetse. `n Reeks trikarboniel komplekse, fac-[Re(L,L’-bid)(CO)3X], is gesintetiseer met `n wye reeks bidentate ligande (L,L’-bid) met sistematies gekose donor atome. Die bidentate ligande sluit in 2,2’-bipiridien-3,3’-dikarboksielsuur, 2,5-piridiendikarboksielsuur, 8- hidroksiequinolien, 5-chloro-8-hidroksiequinolien, 5,7-dimetiel-8-hidroksiequinolien, tropoloon, isatien, 5-nitroisatien, 5-(triflorometoksie)isatien, bensohidroksaamsuur, 3- hidroksieflavoon, chrysien en bis(difenielfosfino)-propielamien, X = reeks monodentate ligande en n = 0, 1. Vier 99mTc komplekse is ook suksesvol gesintetiseer, insluitend fac-[99mTc(2,5- PicoH)(CO)3(H2O)], fac-[99mTc(Trop)(CO)3(H2O)], fac-[99mTc(Cl-ox)(CO)3(H2O)] en fac- [99mTc(DMe-ox)(CO)3(H2O)]. Die isolasie van vyf 99mTc komplekse, waarvan die Rhenium komplekse suksesvol gesintetiseer is, was egter onsuksesvol. Hierdie is net weereens `n bewys dat die ooreenkomste in the chemie van Rhenium en Technetium nie altyd aanvaar kan word nie. Die labiliteit en meganisme van die methanol ligand se substitusie is evalueer deur eenvoudige monodentate nukleofiele. Die metanol substitusie reaksies tussen fac-[Re(2,5-PicoH)(CO)3(MeOH)], fac-[Re(Isa)(CO)3(MeOH)] en fac- [Re(Trop)(CO)3(MeOH)] en ‘n reeks inkomende ligande (bromied ione, jodied ione, piridien, 4-dimetielaminopiridien, imiedasool, tiosianaat ione, tio-ureum en 1-metiel-2- tio-ureum), het almal `n uitruilings assosiatiewe tipe meganisme voorgestel vanuit die negatiewe aktiveringsentropie waardes and postiewe aktiveringsentalpie waardes. Hierna is hoë-druk studies bestudeer en vanuit die resultate is ‘n uitruilings dissosiatiewe meganisme voorgestel, met ‘n defnitiewe afname in die reaksietempo met ‘n toename in druk. Hierdie resultate het weereens bewys dat die enigste manier om sonder enige twyfel `n reaksie meganisme voor te stel, hoë-druk studies en die bepaling van die aktiveringsvolume is. Vir die eerste keer is die water substitusie reaksie van `n kompleks van die vorm fac- [Re(L,L’-bid)(CO)3(H2O)] bestudeer. Die water substitusie reaksie tussen fac- [Re(Trop)(CO)3(H2O)] and tiosianaat ione is gevolg. In totaal het die water substitusie reaksie hoër k1 en K1 waardes as die ooreenstemmende metanol substitusie reaksies. Dit dui op ‘n vinniger en `n meer stabiele produk vir die water substitusie reaksie. Hierdie is uitsonderlike goeie resultate, veral vir die potensiële gebruik in kliniese medisyne. Vanuit die kinetiese studies is uitstekende resultate verkry. `n Duidelike toename in die reaksietempo van die N,O- na die O,O‘-donor bidentate ligand komplekse is verkry wat egter verwag was agv die toename in the elektrondigtheid op die metaal senter en daarom die verswakking van die Re-MeOH binding. Die O,O’-donor bidentate ligande aktiveer die Re(I) metaal senter tot ‘n groter mate as wat vroeër gerapporteer is. Die ‘3+1’ konsep is bewys deur die sintese van fac-[Re(PMAEth-An)(CO)3][NO3], fac- [Re(PMAProp-His)(CO)3][NO3] en fac-[NEt4]/[Na][Re(NTA-An)(CO)3], deur ‘n biologiese aktiewe ligand te ‘link’ op die ruggraat van ‘n tridentate ligand wat reeds gekoordineer is met fac-[Re(CO)3]+. Hierdie resultate maak ‘n wye veld oop vir potensiële radiofarmaseutiese agente. Vier van die tien kristalstrukture in hierdie studie is monodentaat gesubstitueerde komplekse wat verder as bewys dien van die kinetiese eindprodukte.
Thesis (Ph.D. (Chemistry))--University of the Free State, 2011
Keywords: Radioisotopes in pharmacology; Rhenium; Organorhenium compounds; Technetium